2016
DOI: 10.1093/nar/gkw1026
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes in histone acetylation underpin resistance to the topoisomerase I inhibitor irinotecan

Abstract: The topoisomerase I (TOP1) inhibitor irinotecan triggers cell death by trapping TOP1 on DNA, generating cytotoxic protein-linked DNA breaks (PDBs). Despite its wide application in a variety of solid tumors, the mechanisms of cancer cell resistance to irinotecan remains poorly understood. Here, we generated colorectal cancer (CRC) cell models for irinotecan resistance and report that resistance is neither due to downregulation of the main cellular target of irinotecan TOP1 nor upregulation of the key TOP1 PDB r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 63 publications
5
36
0
Order By: Relevance
“…Some clinical studies showed that the anti-tumor effects of irinotecan are due to the cytotoxic activity of SN-38. 21,22 Studies also showed that treatment with irinotecan, fluorouracil, and leucovorin resulted in significantly longer PFS and longer overall survival, as compared with treatment with fluorouracil and leucovorin. 23 In some multicenter randomized trials, the response rate and overall survival were significantly higher in patients in the irinotecan group than in those in the no-irinotecan group; time to progression was also significantly longer in the irinotecan group than in the no-irinotecan one.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies showed that the anti-tumor effects of irinotecan are due to the cytotoxic activity of SN-38. 21,22 Studies also showed that treatment with irinotecan, fluorouracil, and leucovorin resulted in significantly longer PFS and longer overall survival, as compared with treatment with fluorouracil and leucovorin. 23 In some multicenter randomized trials, the response rate and overall survival were significantly higher in patients in the irinotecan group than in those in the no-irinotecan group; time to progression was also significantly longer in the irinotecan group than in the no-irinotecan one.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that knock down of class I HDACs in APL cells induced growth arrest and apoptosis [7,12]. Deregulation of histone acetylation has been found in many neoplasms, particularly in leukemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of acetylation on speci c lysine residues of H3 and H4 is one of the key factors thought to be involved in the progression of carcinogenesis. Moreover, the loss of H4K16 acetylation has been shown to in uence the tumor progression and sensitivity to chemotherapy [11,12]. So, in order to combat these cancers it is important to devise new strategies, one such way is by modulating acetylations levels of histones.…”
Section: Introductionmentioning
confidence: 99%
“…4749 Perturbed histone acetylation stimulates faster access of repair enzymes to the damaged sites and subsequently a higher resistance. 50…”
Section: Discussionmentioning
confidence: 99%